KAJIAN PENGEMBANGAN SISTEM PERTANIAN TERPADU PADA MODEL USAHATANI KONSERVASI BERBASIS TEKNOLOGI HEDGEROW DALAM PENGELOLAAN AGROEKOSISTEM LAHAN LERING DI DATARAN TINGGI NETPALA, TTS - Noldin Abolla; Nimrot E.M Neonufa; Laurensius W. Wardhana; M. Basri (Politeknik Pertanian Negeri Kupang, 2018)
This study aims to determine the feasibility of the Integrated Farming System (IFS) model on conservation farming with Hedgerow Technology which is applied in the Netpala village highland region to land productivity and interactions between components in the system. The study wascarried out in the Agroecosystem Zone V, Netpala plateau, Mollo Utara District, TTS. The method used is the experimental method, through an on-farm research approach together with farmers. The results of the study showed that the conservation farming IFS model with Hedgerow technology could be developed in this region and positively correlated with agricultural productivity and income, ecologically, socio-culturally and economically. Positive interactions are indicated by an ecological and economic feasibility assessment. Economically indicated by the value of B / C ratio> 1 (2.07), which means that the IFS model has economic value and is worth developing. If you wish to write a persuasive, analytical, or comparative essay, contact professional